(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Employment generation remains one of the most significant challenges facing local economies worldwide. In many developing countries, limited access to capital constrains entrepreneurial activity and restricts job creation. Micro-investments have emerged as an effective mechanism for promoting self-employment, supporting small businesses, and stimulating local economic development. This article examines the role of micro-investments in ensuring employment at the local level, analyzing their contribution to entrepreneurship, poverty reduction, financial inclusion, and sustainable community development. The study highlights the experience of developing economies and emphasizes the importance of supportive policies, financial literacy, and institutional cooperation in maximizing the employment effects of micro investment programs.